Learning Media Development of Web-Blog E-learning on Respiratory System Material in Class VIII SMP - Ruqiah Ganda Putri Panjaitan; Titin Titin; Astody Gusta Mandayu* (Universitas Syiah Kuala, 2023)
This research is motivated by the use of powerpoint media which continues to be repeated in the learning process resulting in students feeling bored and unenthusiastic in learning. In addition, schools also have not maximized the use of school internet facilities (wifi) in learning, therefore innovation in technology-based learning media is needed.This study aims to evaluate the validity of an e-learning media-based web blog on respiratory system material. The method used in this study is the research and development (RD) method and the ADDIE model consists of 5 stages namely analyze, design, develop, implement, and evaluate. The sample of the research is class VIII C students of SMP which consisted of 39 students. The instrument used in this study is the form of media validation. The eligibility of an e-learning media-based web blog is measured through a validity test by 6 validators consisting of material and media experts. The materials expert consisted of 2 lecturers of biology education and 1 science teacher. Media experts consist of 2 lecturers of media specialists and 1 teacher of information communication technology. The research results showed that an e-learning media-based web blog on the respiratory system material is appropriate to be used as a learning medium and become a new alternative media for science teachers with an average score of material expert validation at 3.45 and a media expert validation at 3.84